Congenital Maxillomandibular Synechia with Multiple Malformations in a Very-Low-Birth-Weight Infant: A Case Report - Uchi, Ryosuke; Koto, Mayu; Nakao, Atsushi; Hosokawa, Miku; Ukawa, Toshiko; Tsurisawa, Chisa; Hisaeda, Yoshiya; Amagata, Shusuke (American Journal of Perinatology Reports, 2023)
Congenital maxillomandibular synechia is a rare malformation that is characterized by a fusion of the maxilla and mandible. The fusion is fibrous or bony and prevents mouth opening, which causes difficulties in feeding and occasionally in breathing. Although extremely rare, neonatologists must understand the disease because it can be fatal and require emergency treatment after birth. We report the case of a very-low-birth-weight (VLBW) infant with congenital maxillomandibular synechia and other malformations, including cleft palate, syndactyly, and cryptorchidism. The patient presented with extremely limited mouth opening, and endotracheal intubation seemed impossible; fortunately, the patient did not have respiratory distress syndrome. The patient underwent surgical release of the fibrous bands on days 10 and 17, and good mouth opening was achieved. The patient was able to consume breast milk orally and was discharged home at a corrected gestational age of 1 month without recurrence of difficulty in mouth opening or any sequelae. This is the first reported case of a VLBW infant with congenital maxillomandibular synechia who required more complicated management of feeding, surgical intervention, and anesthesia.
Keywords: congenital maxillomandibular synechia; fibrous or bony fusion; difficulty in feeding and breathing; popliteal pterygium syndrome